TEACHING ENGLISH PRONUNCIATION USING FILM - Dyah Indri Fitri Handayani (Journal of English and Education, 2017)
This study aimed to discover (1) whether the use of film is effective to improve students’ pronunciation ability and (2) the students’ response toward film in improving their pronunciation. The study applied a quantitatve study in a private High School in Bandung. The participants of this study were class X IPA 2 and X IPS 2 with total 60 students. The data were gathered from test and interview. The result of this study showed that the use of film in teaching English pronunciation does not give major improvement. However, the students responded positively toward film as teaching media. Furthermore, the use of film in teaching enhances students’ motivation in learning English. This research suggests that the use of film could be useful for educational purpose.